Effectiveness Of Munazharah Lectures To Improve Speaking Skills (A Case Study At The UMY Yogyakarta Arabic Language Education Department) - Miftahull Jannah; Ahmad Suyudi; imannudin Sendi Perdana; Nyanyang Septian; Alfin Khalil Ghibran; Arisna Rukmana Putri (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2023)
Education plays an important role in creating a learning atmosphere and learning process that is needed by every human being. One of the skills that must be possessed by students is speaking skill. This study aims to analyze the effect of applying the munazarah method on the speaking skills of Arabic language education study program students at the Muhammadiyah University of Yogyakarta (UMY) in the munazarah course. Where from the results of observations the researchers saw that the students of Yogyakarta Muhammadiyah University seemed to really master Arabic well. The data collection techniques and tools used in this study were interviews and direct observation. Based on the research results, it can be concluded the following things. The results of their interviews stated that before entering semester 2, where there was no munazarah course to be precise, they were not very good at mastering Arabic speaking skills. As a result of their own expressions when there is reflection and training at each meeting, their Arabic speaking skills in this munazarah course are increasing in semester 5 so that they can implement it through speeches, poetry and even compose and compose Arabic texts by themselves.